A Good Strategy to Pull the Needy Out of Poverty? Contracting Out the Public Employment Services for the Poor in Taiwan. Issue 3 (September 2014) - Lin, Hung‐Yang; Li, Shu‐Jung; Hung, Hui‐Fen
<x xml:space="preserve">Abstract</x> This article intends to clarify the needs of those economically vulnerable people in Taiwan, and to investigate whether referring the poor to the "contracted‐out" Public Employment Services (PES) and pushing them back to full‐time employment would be an effective way to help them out of poverty. For this purpose, it applies both quantitative and qualitative methods. The quantitative part is mainly done by questionnaires collected from 400 low‐income and mid‐low‐income respondents, and the qualitative part is composed of focus groups and extended interviews of respondents who are low‐ and mid‐low incomers. This research found that the employment services, family policy, and social provisions in Taiwan did not meet poor people's needs and therefore were unable to help them out of poverty. In addition, it found that the arrangement of the PES may result in the inefficiency and poor quality of services. Therefore, the governance of the PES may need to be reconsidered.